Obesity as a Predictor of Outcomes in Type III and Type IV Supracondylar Humerus Fractures. Issue 11 (November 2021) - Nazareth, Alexander; Schur, Mathew; Schroeder, Amanda J.; Whitlock, Patrick W.; Skaggs, David L.; Goldstein, Rachel Y.
Abstract : Objectives: To investigate the association of obesity with fracture characteristics and outcomes of operatively treated pediatric supracondylar humerus fractures. Design: Retrospective multicenter. Setting: Two Level I pediatric hospitals. Patients: Patients (age <18 years) with operatively treated Gartland type III and type IV fractures 2010–2014. Intervention: Closed or open reduction and percutaneous pinning of supracondylar humerus fractures. Main Outcome Measure: Incidence of Gartland IV fracture, preoperative nerve palsy, open reduction and complication rates. Results: Patients in the obese group had a significantly higher likelihood of having a Gartland IV fracture (not obese: 17%; obese: 35%; P = 0.007). There was a significantly higher incidence of nerve palsy on presentation in the obese group (not obese: 20%; obese: 33%; P = 0.03). No significant differences were found between groups regarding incidence of open reduction, compartment syndrome, and rates of reoperation. Conclusions: The present study demonstrates that obese children with a completely displaced supracondylar humerus fractures have an increased risk of Gartland type IV and preoperative nerve palsy compared with normal weight children. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.